Design and analysis of highspeed electronics for electro optical payload of small satellites - Naveed, Mohammad (Department of Electrical Engineering, 2023)
With the increase in the resolution of the Earth observation satellites, the cameras on these satellites require more detectors to fulfil the swath need and also the image sensors have to operate at a very high-speed with the sensor electronics requiring faster clock rates and larger bandwidth. The sensor data handler has to transfer a large amount of data to the spacecraft in real time incorporating the outcomes of the signal integrity and power integrity analysis in the design. High-speed analysis is an important consideration for high resolution cameras and is often performed on the satellites. This research work aims towards presenting the design and analysis of high-speed electronics for small Earth observation satellites. A methodology will be defined for the designing of high-speed electronics that will involve both the pre-layout and post-layout designs for signal and power integrity analysis. The proposed research work also provides the pre-layout and post-layout signal integrity analysis of the high-speed electronics and interfaces and it will also validate the signal integrity performance of the module by comparing it with standard performance parameters. Similarly, we will perform a pre-layout and post-layout power integrity analysis of the high-speed electronics and interfaces and its effects on the power lines and power planes.